Atención y fluidez verbal en un niño con trastorno fonológico. - Paccha Fernandez, Ana Paola; Loayza Espinoza, Nicole Del Cisne (Machala: Universidad Técnica de Machala, 2025)
This research addresses the following question: What is the relationship between attention and verbal fluency in a 10-year-old child with a phonological disorder? Based on this, the general objective was defined as follows: to analyze the relationship between attention and verbal fluency in a 10-year-old child with a phonological disorder.To achieve this aim, a qualitative approach with a descriptive design was adopted, allowing for a detailed and contextualized understanding of the case under study. The techniques employed included semi-structured interviews, direct observation, and the administration of standardized psychometric tests. Among the instruments applied were the NEUROPSI Attention and Memory test, the PROLEC-R (for assessing reading and linguistic processes), and the CARAS-R psychometric test (to quantitatively evaluate attention and perceptual speed).The results revealed that the child exhibits severe impairments in attention processes and verbal fluency. A high level of distractibility in response to immediate environmental stimuli was observed, which hindered sustained concentration and the appropriate following of verbal instructions. In the language domain, marked difficulties were noted in correctly pronouncing and producing words, due to a systematic alteration of speech sounds that interferes with effective communication.These findings indicate a direct relationship between attention and verbal fluency, underscoring the importance of personalized psycho-pedagogical interventions that simultaneously address attentional and linguistic aspects to foster optimal learning development.
En el presente trabajo de investigación aborda el siguiente problema: ¿Qué relación existe entre la atención y la fluidez verbal en un niño de 10 años con trastorno fonológico? A partir de esta interrogante, se planteó como objetivo general: analizar la relación existente entre la atención y la fluidez verbal en un niño de 10 años con trastorno fonológico.Para poder alcanzar este propósito, se empleó un enfoque cualitativo con un diseño descriptivo, que permitió una comprensión detallada y contextualizada del caso en estudio. Las técnicas utilizadas fueron la entrevista semiestructurada, la guía de observación, y la aplicación de pruebas psicométricas. Entre los instrumentos aplicados se encuentran el Test Neuropsi: Atención y Memoria, el PROLEC-R (para evaluar procesos lectores y lingüísticos) y el Test Psicométrico CARAS-R (para medir atención y velocidad perceptiva de manera cuantitativa).Los resultados obtenidos muestran que el niño presenta alteraciones severas en los procesos de atención y fluidez verbal. Se evidenció una alta distracción frente a estímulos del entorno inmediato, lo que dificulta su concentración sostenida y el seguimiento adecuado de instrucciones verbales. En el área del lenguaje, se observaron dificultades marcadas para pronunciar y emitir correctamente las palabras, debido a una alteración sistemática de los sonidos del habla que interfiere en la comunicación efectiva. Estos hallazgos reflejan una relación directa entre las variables de atención y la fluidez verbal, lo cual destaca la importancia de una intervención psicopedagógica personalizada que aborde simultáneamente los aspectos atencionales y lingüísticos para favorecer un mejor desarrollo dentro del aprendizaje.
Keywords: ATENCIÓN; FLUIDEZ VERBAL; TRASTORNO FONOLÓGICO; INFANTE; LENGUAJE; PRONUNCIACIÓN; DISTRACCIÓN; PRUEBAS PSICOMÉTRICAS